Clinical Metagenomic Next-Generation Sequencing for Diagnosis of Secondary Glaucoma in Patients With Cytomegalovirus-Induced Corneal Endotheliitis - Wu, Wei; Jiang, Hua; Zhang, Ying; Zhou, Yang; Bai, Guannan; Shen, Lingwei; Zhou, Hongwei; Chen, Xiangjun; Hu, Lidan (Frontiers in Microbiology, 2022)
According to growing scientific evidence, secondary glaucoma is linked to the corneal endothelial loss. Cytomegalovirus (CMV) has been identified as the most common herpes virus in corneal endotheliitis patients. Early detection is critical in preventing endothelial cell loss, which can further lead to corneal decompensation. However, routine culture and polymerase chain reaction (PCR) cannot distinguish the endothiliitis that is caused by the CMV from that which is induced by the Varicella Zoster Virus (VZV) or Herpes Simplex Virus (HSV). This may result in inappropriate treatment, which may prolong or aggravate the condition. We compared the sensitivity and specificity of PCR and mNGS in the aqueous humor of patients with suspected CMV endotheliitis in this study. Our results showed that three out of seven (42.9 %) of our patients were positive for CMV, whereas mNGS had a 100% detection rate of CMV. Our findings imply that mNGS could be a useful diagnostic tool for CMV-induced endotheliitis.